Trends of science technology engineering mathematics (STEM)-based learning at elementary school in Indonesia - Fitri Nuraeni; Yopi Malagola; Suko Pratomo; Hafiziani Eka Putri (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This research investigates the results of studies related to the implementation of Science Technology Engineering and Mathematics (STEM)-based learning at elementary schools in Indonesia. Using the Systematic Literature Review (SLR) with meta-synthesis model, this research selects research articles related to STEM-based learning at elementary school in Indonesia from google scholar and google site as sources for primary data and secondary data, respectively. After reviewed through inclusion and exclusion criteria evaluated by quality assessments, 15 scientific articles published within 2015 to 2020 are analysed.  Findings show that many studies have great interest in developing STEM-based teaching and learning materials, while others focus on identifying the impact of STEM-based learning on various learning achievements such as creative thinking skills, critical thinking skills, basic questioning skills, and scientific literacy, and learning achievement in general.